Estudio del efecto de la cordia dentata y malachra alceifolia de origen caribeño sobre pseudomonas aeruginosa (2020)
Introduction: The existence of multidrug-resistant bacteria to antibiotics has become a real problem for the health sector worldwide. In the search for solutions for these events, the option of returning to the implementation of herbal medicine as an antimicrobial alternative has emerged. Objective: The present work evaluated the effect of the chloroform extracts of the Cordia dentata and Malachra alceifolia plants, on crops of the strain Pseudomonas aeruginosa multidrug-resistant drug to antimicrobials. Methodology: To evaluate the effect of extracts of Cordia dentata and Malachra alceifolia on cultures of the multidrug-resistant strain of Pseudomonas aeruginosa, the method of minimal inhibitory concentration in microplate was used and the readings were determined by D.O. To validate the results, the diffusion method on Mueller-Hinton agar was used. Gentamicin was used as a positive control. Results: The results did not show the bactericidal or bacteriostatic activity of the two extracts evaluated on the multidrug-resistant strain of Pseudomonas aeruginosa. Conclusion: The complete extracts obtained from the chloroform solvent were inefficient against multidrug-resistant strains of Pseudomonas aeruginosa, as they did not show any bacteriostatic or bactericidal effect against this microorganism.